(3QSGdI aj GdcdGe Ydi GdMGFW GdefgOes - (3eMeO Hf HjQe GdKGfjs
(3ChdgG (B:s
(3GdMeO ddg gPG JdNjU GdcdGe ai GdMGFW GdefgOe EPG JfGRY TQcGDg s
(3BNQgG (B:s
(3de jhQO cdGege ajgG ef cOQ GdJYGQV s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs